Transformation of the Advocate Organisational System in Indonesia: Multi-Bar Implications for Enforcement of Professional Ethics - Fatiha, Nilam Amalia (Yayasan Cahaya Generasi Positif, 2025)
This research analyses the transformation of the Indonesian advocate organisational system from single-bar to multi-bar and its implications for upholding professional ethics. Even though the 2003 Law on Advocates mandates a single bar, internal conflicts and organisational resistance triggered multi-bar legitimisation through KMA Letter No. 73/2015. Using a normative-juridical-empirical qualitative approach, this study integrates analysis of regulatory documents and interviews with practitioners to explore the historical and contemporary dynamics of the advocate organisational system. The research results show that the multi-bar system positively democratises the profession, reduces regulatory monopolies, and increases access to legal services in remote areas. However, significant challenges arise through disparities in organisations to avoid sanctions and standardisation of organisational consistency. Enforcing harmonisation efforts have been made to harmonise the labelling. Harmonisation efforts have been studied, recommending a multi-bar framework, establishing an independent national ethics institute, and strengthening collaboration between organisations through sacrificing specialisations.